Implementation of Data Mining in Grouping Data of the Poor Using the K-Means Method - Nera Mayana Br. Tarigan; Santa Elisa Br. Tarigan; Alfrida P. Simatupang (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Processed, especially data on people who are classified as poor. So that the provision of assistance from the central government or donors is right on target. In village governance, data processing often occurs that is not good and does not use technology, so if any assistance is provided it will make it difficult for the village government to distribute it to poor people. This study aims to classify the data of the poor by implementing data mining and applying the K-means algorithm for grouping data of the poor by applying the K-means algorithm. The research method used is observation research methods and direct interviews to obtain problems and data needed in data processing. The data used is community data. The results of the study obtained that the poor community group was divided into three parts, namely: Poor, Simple, and Able. So it can be seen that there is no shift or change in the data group towards the center of the cluster.